Capital Account Policies, IMF Programs and Growth in Developing Regions - Zorobabel Bicaba; Zuzana Brixiova; Mthuli Ncube (Institute for the Study of Labor (IZA), 2015)
This paper develops an adaptive learning model under uncertainty that examines evolution of capital account polices over time and across developing regions. In the framework, countries' past experiences and IMF programs influence policymakers' beliefs about the impact of capital account liberalization on growth, under the 'Mundell's trilemma constraint. The model, calibrated to data for Africa, Latin America and developing Asia, reflects relatively well capital account policies adopted in 1980-2010. It shows that even more developed countries with liberalized capital accounts may revert to controls under large output shocks. The outcomes of capital account switches are better and closer to policymakers' expectations in countries with the IMF programs, underscoring the role of complementarity of policies.
Keywords: F43; O4; O43; O55; 330; adaptive learning; dynamics of capital account policies; growth; IMF programs